Usaha Kreatif Berbasis Jagung sebagai Alternatif untuk Meningkatkan Ekonomi di Desa Daenaa, Limboto Barat - Tangio, Julhim S; Husain, Rustam I.; Laliyo, Lukman Abdul Rauf; Mohamad, Erni; Zakaria, Perry; Kilo, Ahmad Kadir (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service project seeks to boost the added value and welfare of maize producers through the creation of corn flour products. Corn flour products have tremendous potential in enhancing the economics of the community, especially corn farmers, by delivering food products manufactured from maize that have wonderful tastes and high nutritious value. In addition, the food products created are very popular and have vast market potential. Through the training and mentoring approach of the IbM activities, the community obtained important information and knowledge, enabling them to create innovation and enterprise in the maize sector. The outcomes of this activity demonstrate that this service program not only enhances the skills and knowledge of the community, but also helps the improvement of their economic wellbeing in a sustainable manner.